On three new species of Cypretta Vávra, 1895 (Crustacea: Ostracoda) from the Yucatan Peninsula, Mexico - Cohuo-Durán, Sergio; Elías-Gutiérrez, Manuel; Karanovic, Ivana (Zootaxa, 2013)
Three new species of the genus Cypretta Vávra, 1985 are described from Southern Mexico, representing the first record of the genus in the country. Cypretta campechensis n. sp. is closely related to Florida and North Carolina species such as C. nigra Furtos, 1936, C. brevisaepta Furtos, 1934 and C. bilicis Furtos, 1936. Cypretta spinosa n. sp. is related to the North and South American species C. intonsa Furtos, 1936 and C. vivacis Würdig & Pinto, 1993, but also to some Aus-tralian and South-East Asian Islands ones, such as C. obfuscata Victor & Fernando, 1981 and C. raciborskii (Grochmalicki, 1915). The last species described herein, Cypretta maya n. sp., is closely related to the South-East Asia islands, Australian and north Indian species, in particular to C. hirsuta Henry, 1923, C. longidactyla Victor & Fernando, 1981, and C. patialensis Battish, 1982.